Labor Informalization and Social Problems in Indonesia in Gender Equality Study (Case Study of Layoffs as the Effect of Digitalization in Cirebon City in 2019) - Ratna Puspitasari; Apriyanda Kusuma Wijaya (Sunan Kalijaga: International Journal of Islamic Civilization, 2020)
As of March 31, 2019, the Cirebon City Giant Hyper market has been declared closed and does not carry out trading activities. Employees who are dominated by women are threatened with being dismissed and this creates widespread social problems in the community. As a result of these layoffs, it has led to the growth of labor informalization with the proliferation of street workers (PKL) or independent workers which will cause chaos in the arrangement of big cities, which will have an impact on social problems. This study tries to analyze the gender equality study of the Marx model with an ethnographic approach, trying to trace the causes and effects of the informalization that afflicts female workers in the city of Cirebon.